2007
DOI: 10.1007/s00268-006-0759-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for Cholesterol Management

Abstract: Over the last 50 years, several attempts have been made to harness the power and economy of vaccines in the fight against cardiovascular disease. Vaccines directed to lipoproteins, cholesterol itself, and molecules involved in cholesterol metabolism have all demonstrated success in modifying progression of disease in animal models of atherosclerosis. One vaccine that elicits antibodies to cholesteryl ester transfer protein has also progressed into the realm of human clinical testing. This review summarizes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Vaccines against lipoproteins, cholesterol itself, and molecules involved in cholesterol metabolism have all proved helpful in modifying the course of sickness in animal models of atherosclerosis. One vaccine that generates antibodies against cholesteryl ester transfer protein has also advanced into the domain of human clinical testing [ 74 ]. PCSK9 inhibitors in particular have had a significant impact on clinical practice; angiopoietin-like 3 (ANGPTL3) inhibition has recently been shown.…”
Section: Pcsk9 Vaccinesmentioning
confidence: 99%
“…Vaccines against lipoproteins, cholesterol itself, and molecules involved in cholesterol metabolism have all proved helpful in modifying the course of sickness in animal models of atherosclerosis. One vaccine that generates antibodies against cholesteryl ester transfer protein has also advanced into the domain of human clinical testing [ 74 ]. PCSK9 inhibitors in particular have had a significant impact on clinical practice; angiopoietin-like 3 (ANGPTL3) inhibition has recently been shown.…”
Section: Pcsk9 Vaccinesmentioning
confidence: 99%
“…Given these results, the authors have begun to develop a new vaccine, using a more immunogenic antigen (CETi-2). Their preliminary data have shown that, in animal studies, this vaccine can elicit higher titers of anti-CETP antibodies than CETi-1 [28]. In addition, Gaofu et al have used two types of CETP vaccines, one composed of the 26 C-terminal amino acids of human CETP and another DNA vaccine containing CpG motifs as an adjuvant and showed a reduction of atherosclerotic plaques in a rabbit model of atherosclerosis [29][30][31][32] (Table 3).…”
Section: Vaccines Against Targets Of Cholesterol Metabolismmentioning
confidence: 95%
“…59,60 These vaccines have been mainly developed to target lipoproteins, cholesterol itself, or molecules involved in the metabolism of cholesterol. [61][62][63][64][65]…”
Section: Vaccines For Dyslipidemia and Cholesterolmentioning
confidence: 99%